Comparative assessment of the exosomal tumor-associated microRNA levels in blood plasma and ascitic fluid in ovarian cancer patients - E. I. Dzhugashvili; N. V. Yunusova; A. I. Yalovaya; A. E. Grigorieva; E. E. Sereda; L. A. Kolomiets; S. N. Tamkovich (Успехи молекулярной онкологии)
Introduction. Ovarian cancer (OC) is one of the malignant neoplasms of the female reproductive system with a high mortality rate. Currently used tumor markers of this pathology do not have high sensitivity and specificity. In this regard, promising areas of molecular oncology are the study of the mechanisms of carcinogenesis of OC and the search for new biomarkers of liquid biopsy for early non-invasive diagnosis of neoplasms. It is known that tumor cells actively secrete exosomes into the extracellular space, which include biologically active molecules involved in carcinogenesis and claiming to be diagnostic markers. It was previously shown that microRNA-24 (miR-24) and microRNA-101 (miR-101) are transported as part of exosomes in OC and are involved in the degradation of the extracellular matrix, stromal remodeling, angiogenesis, and cancer cell motility.Aim. To evaluate the representation and diagnostic significance of miR-24 and miR-101 in plasma exosomes and ascitic fluid of OC patients.Materials and methods. The study included blood and ascitic fluid samples from OC patients (n = 20) and blood samples from healthy women (n = 19). The exosomal nature of the vesicles was confirmed by transmission electron microscopy, nanotracing analysis, and flow cytometry. After isolation of exosomal RNA, the relative level of miRNA was determined using reverse transcription and real-time polymerase chain reaction.Results. The highest concentration of exosomes was found in the ascitic fluid of OC patients, while the concentration of exosomes in the blood plasma of these patients was significantly higher than in healthy women. Relative levels of miR-24 and miR-101 in exosomes of blood plasma of healthy women were significantly higher than in exosomes of blood plasma and ascitic fluid of OC patients; at the same time, the levels of these miRNAs in exosomes of plasma and ascitic fluid of patients did not differ significantly.Conclusion. The results obtained confirm the promise of exosomal miR-101 and miR-24 for the diagnosis of OC by liquid biopsy.